Oncology boards flash review - Worden, Francis P. (Demos Medical Pub., 2013)
Coverage extends across the range of major hematologic malignancies and solid tumors, as well as reviews of pharmacology, biostatistics, genetics and tumor biology, and survivorship and palliative care. Each topic is consistently presented with the key points summarized in bullet point form for easy recall. Question-based headings enable the reader to systematically review and assess his knowledge.